AB0106 The Small Gtpase Rhoa Signalling is Upregulated in the Cartilage of Patients with Knee Osteoarthritis Through the Phosphorylation of Myosin Light-Chain (MLC) Phosphatase Regulatory Unit MYPT-1 Induced by ERK: In Vivo and in Vitro Studies. (9th June 2015) - Pérez-Baos, S.; Andrés-Bergόs, J.; Barrasa, J.I.; Larrañaga-Vera, A.; Calvo, E.; Sanz-Gomez, P.; Sánchez-Biezma, E.; Herrero-Beaumont, G.; Largo, R.
Abstract : Background: Osteoarthritis (OA) is characterized by progressive destruction of articular cartilage and changes in chondrocyte phenotype. The signalling of RhoA, a small GTPase protein, has a critical role in a range of cellular functions, including cytoskeleton rearrangement, being essential in focal adhesions and cell-matrix interactions. Several studies described the involvement of RhoA signalling in the healthy chondrocyte phenotype induced by interleukin (IL)-1α, a pro-catabolic cytokine locally increased in OA. Dysregulation of this signalling pathway could play an important role in the development of OA. Objectives: We aimed to study RhoA signalling pathway in human OA cartilage, and to establish the underlying mechanism involved in its regulation employing IL-1α in "in vitro" studies. Methods: Human OA cartilage was isolated from the knee of OA patients during joint replacement surgery while healthy cartilage was obtained from the knee of age and sex-matched healthy donors. In vitro studies were also conducted on human OA chondrocytes in culture (HOC). HOC were stimulated with 10 ng/ml IL-1α at different periods of time. Results: We observed increased protein levels of RhoA and its effector kinase ROCK1 in the cartilage of OA patients when compared to healthy cartilage. Cytoskeletal arrangement is regulated through MYPT-1 phosphorylation -a regulatory subunit of MLC-phosphatase- by different kinases, including ROCK. OA cartilage also showed an increase in both the total and the phosphorylated (Thr-853) form of 70 KDa MYPT-1, compared to healthy cartilage. In addition, we found an increased phosphorylation of the final effector MLC in OA cartilage. In order to further elucidate the mechanism underlying RhoA activation in OA cartilage, we first studied whether IL-1α was able to mimic the RhoA signalling activation in HOC in culture. IL-1α induced a significant increase in RhoA synthesis that was not linked to ROCK1 activation. We also observed an increase in the presence and phosphorylation of the 70KDa MYPT-1 form, with a simultaneous decrease in the 110 KDa MYPT-1 form. ROCK inhibition was unable to prevent MYPT-1 phosphorylation induced by IL-1α in HOC. However, we did observe lower phosphorylation levels when using an ERK1/2 inhibitor. IL-1α induced RhoA recruitment to the HOC membrane, assessed by immunofluorescence. Phalloidin staining revealed that IL-1α triggered formation of stress fibers and the loss of focal adhesion in HOC. Both stress fiber formation and focal adhesion loss were improved by the ERK1/2 inhibitor. Conclusions: RhoA signalling is enhanced in the cartilage of OA patients, probably mediated by an increase in MYPT-1 phosphorylation. Stimulation of HOC with IL-1α is able to mimic these changes. However, MYPT-1 phosphorylation in HOC appeared to depend on ERK1/2, rather than on ROCK, as observed in OA cartilage. Further studies are needed to confirm the role of ROCK and ERK1/2 in RhoA activation in chondrocytes. Our results support the hypothesis that RhoA signalling pathway could be a potential therapeutic target in OA. Disclosure of Interest: None declared